Nanobiotechnology for the Prevention of Dialysis-related Amyloidosis - Stamopoulos, D.; Bouziotis, P.; Benaki, D.; Zirogiannis, P.N.; Kotsovassilis, K.; Belessi, V.; Dalamagas, V.; Papadopoulos, K. (THERAPEUTIC APHERESIS AND DIALYSIS, 2009)
Dialysis-related amyloidosis is related to the inefficient removal of beta(2)-microglobulin (beta(2)-m) that is mainly responsible for the formation of amyloid fibrils deposited on the joints and in the heart, blood vessels and digestive system. Magnetically assisted hemodialysis (MAHD) can be used for the prevention of dialysis-related amyloidosis. MAHD is based on ferromagnetic nanoparticle-targeted binding substance conjugates (FN-TBS Cs) that should be administered to the patient before the dialysis session. The TBS should have a high affinity for beta(2)-m so that the conjugates bind with the beta(2)-m in the bloodstream. The complex FN-TBS-beta(2)-m will be selectively removed during dialysis by means of a "magnetic dialyzer" that is installed at the dialysis machine in series to the conventional dialyzer. We have examined the in vitro applicability of MAHD by employing biocompatible Fe3O4 and bovine serum albumin (BSA) as constituents of the FN-TBS Cs. We evaluated the binding capacity of both bare Fe3O4 FNs and Fe3O4-BSA Cs for beta(2)-m concentrations ranging from mild to severe conditions. Finally, we conducted mock-dialysis experiments for the evaluation of several technical issues related to MAHD. beta(2)-m is adsorbed onto the Fe3O4-BSA Cs not only almost instantly, but also very efficiently. The employed Cs do not chemically interact with the materials used in standard dialyzers, as agglomerates were not observed in the capillaries of the conventional dialyzers. MAHD may become an efficient modality for the prevention of dialysis-related amyloidosis because beta(2)-m concentrations ranging from mild to severe conditions can be adequately handled.